Anaphylactic shock after Ranitidine – a Case report: Anafilaktični šok po Ranitidinu – poročilo o primeru - Željko, Tadej; Sinkovič, Andreja (Acta Medico-Biotechnica, 2021)
Purpose: Anaphylactic shock is a severe, unexpected, life-threatening generalized hypersensitivity reaction that is usually triggered by antigens such as food, venom or drugs. Among drugs, ranitidine is considered safe and is even used in allergic reactions to decrease skin rash. However, in rare cases, ranitidine can provoke anaphylaxis or even anaphylactic shock.Case report: We present the case of a 30-year-old woman with abdominal pain, treated with i.v. bolus of ranitidine after previous occasional oral ranitidine ingestion. Within minutes, she developed symptoms and signs of anaphylactic shock. Immediate treatment was initiated with i.v. adrenaline, fluid infusion, and i.v. hydrocortisone and clemastine. After admission to the intensive care unit, treatment was continued, includingi.v. vasopressors. Intubation and mechanical ventilation were needed because of acute respiratory failure. After 2 days, the situation resolved completely. After she was extubated, the patient could breathe spontaneously without the need for additional oxygen. She was discharged without any sequelae within a few days.Conclusion: We conclude that even ranitidine, which has been used safely for many years, can trigger anaphylaxis and/or anaphylactic shock. In cases of anaphylactic shock, treatment with vasopressors, intubation and mechanical ventilation is needed to preserve life.
Keywords: anaphylaxis; ranitidine; anaphylactic shock; allergy